Ó César!: poder, ficcionalidade e narrativa na pós-antiguidade - Igor Barbosa Cardoso (2013)
This thesis aims to develop some aspects of what a given historiography, when studying time experiences in the second century, has named post-Antiquity. Investigating some samples of the fictional prose such as the invention of a discourse genre, that is, the novel, and comparing them to philosophical, historical and rhetorical productions in the same period, I seek to analyze the notion of time consciousness through the limits and possibilities of the writing of history, description of a historicity regime that already is not ancient, but still not defined. It is suspected, on one hand, that the Pax Romana under the Antonine emperors expressed the composition of distinct interests and, on the other hand, that the novels have been read by a univocal logic, since I believe, in this thesis, that humor was capable of rebuilding the field of political dispute in times of depletion of the imperial institutions. It comes, in fact, to the thinking of post-antiquity as the articulation of prose narrative, which implies the consciousness of fictional representations ambivalence, to inscribe in language a new political behavior.